Citrus peelminer Marmara gulosa Guillèn and Davis (Insecta: Lepidoptera: Gracillariidae) - Lukasz L. Stelinski (EDIS)
The citrus peelminer is a dark-gray moth with mottled white and brown markings and about 4 mm in length. This moth is considered native in the United States, attacking willow. It is believed that a host-shift occurred to multiple non-native plants including all varieties of citrus and certain ornamentals, such as oleander. Citrus peelminer has been reported to occur in low numbers in Florida and at least three Marmara species have been identified in the state. Recent evaluations of an experimental pheromone lure that is still under development by researchers at the University of California, Riverside have confirmed captures of citrus peelminer (Marmara sp.) in Polk County, Florida. This 3-page fact sheet was written by Lukasz L. Stelinski and published by the UF Department of Entomology and Nematology, April 2013.